Chorioamnionitis and neonatal morbidity: current perspectives - Galán Henríquez GM; García-Muñoz Rodrigo F (Dove Medical Press, 2017)
Gloria Mercedes Galán Henríquez, Fermín García-Muñoz Rodrigo Service of Neonatalogy, Complejo Hospital Universitario Insular Materno Infantil de Canarias, Las Palmas de Gran Canaria, Spain Abstract: The term chorioamnionitis (CA) is commonly used to refer to different clinical or pathological conditions characterized by an infectious and/or inflammatory process that affects primarily the chorioamniotic membranes, but also the amniotic fluid, vessels of the chorionic plate, and, eventually, the umbilical cord (funisitis) and the fetus. Its incidence is higher at lower gestational ages, and the main mechanism is believed to be the ascending bacterial infection from the maternal genital tract. It can be diagnosed by clinical criteria, amniotic fluid examination for inflammatory mediators, and/or isolation of microorganisms, or by histopathological examination of the placenta. CA is an important cause of stillbirth and is related to an increased incidence of premature rupture of membranes, preterm delivery, and adverse maternal and neonatal outcomes such as early-onset neonatal sepsis and necrotizing enterocolitis. An independent causal association to other neonatal morbidities is more controversial. The heterogeneity in the diagnostic criteria and in the operative definitions for morbidity makes comparison of studies difficult, and results are inconsistent. In addition, the intensity and duration of the process are usually not considered. For all these reasons, evidence-based recommendations for the management of mother and infant under these circumstances are difficult to establish, and clinical practice varies widely. Keywords: clinical chorioamnionitis, histological chorioamnionitis, stillbirth, prematurity, morbidity, mortality